Pengaruh Jumlah Anggota, Partisipasi Anggota dan Lingkungan Koperasi Terhadap Keberhasilan Koperasi Di Kecamatan Klojen Kota Malang - Trixie Anatasya Bella Safitri; Nur Diana; Junaidi Junaidi (e_Jurnal Ilmiah Riset Akuntansi, 2023)
The goal of this study was to ascertain how the success of cooperatives in the Klojen area of Malang city was influenced by the number of members, member engagement, and cooperative atmosphere. All of the cooperatives in the Klojen District region make up the study's population, which was sampled using the questionnaire distribution method. According to the study's test results, the number of members, member participation, and the cooperative atmosphere all have an impact on how successful cooperatives are. The outcome of partial testing of the variable "Number of Members" is favorable for the cooperative. Partially testing the Member Participation variable has an impact on the cooperative's success. The success of cooperatives is influenced by partial testing of cooperative environment variables.Keywords: Number of members, member participation, cooperative environment, cooperative success.